The impact of Shariah supervisory board characteristics on internal Shariah auditor Effectiveness, role of Management Support as a Moderator in Islamic financial institutions in the United Arab of Emirates - Alani, Hussein Alwan Dhahir (Tanjong Malim, 2023)
The impact of Shariah supervisory board characteristics on internal Shariah auditor Effectiveness, role of Management Support as a Moderator in Islamic financial institutions in the United Arab of Emirates by Alani, Hussein Alwan Dhahir